International Spill-Over of Technologies and Regional Agglomeration and Development - Gries, Thomas (Science Research Management)

Obstacles Facing German Enterprises in South Africa - Gilroy, Bernard Michael; Gries, Thomas; Naudé, Willem A.; Schmidt, K.-H. (Multinational Enterprises, Foreign Direct Investment and Growth in Africa: South African Perspectives)

Interbank market frictions, international banks and growth - Gries, Thomas; Sievert, Gerhard; Wieneke, Axel (International Economics and Economic Policy)

Anreizkompatibilität als zentrales Element eines neu gestalteten Gesundheitsmarktes - Gries, Thomas; Langeleh, Dirk (Perspektiven der Wirtschaftspolitik)

Evolutionary equilibrium in Tullock contests: spite and overdissipation - Hehenkamp, Burkhard; Leininger, W.; Possajennikov, A. (European Journal of Political Economy)

Neue Wachstums- und Innovationspolitik in Europa - Gries, Thomas; Jungmittag, Andre; Welfens, Paul J.J.

Equilibrium Selection in the Two-Population KMR Model - Hehenkamp, Burkhard (International Game Theory Review)

Bidding for envy-freeness: A procedural approach to n-player fair-division problems - Haake, Claus-Jochen; Raith, Matthias; Su, Francis Edward (Social Choice and Welfare)
We develop a procedure for implementing an efficient and envy-free allocation of m objects among n individuals with the possibility of monetary side-payments,assuming that players have quasi–linear utility functions. The procedure eliminates envy by compensating envious players. It is fully descriptive and says explicitly which compensations should be made,and in what order. Moreover,it is simple enough to be carried out without computer support. We formally characterize the properties of the procedure,show how it establishes envy-freeness with minimal resources,and demonstrate its application to a wide class of fair-division problems.

Catching‐Up, Falling Behind and the Role of FDI:A Model of Endogenous Growth and Development - Gries, Thomas (South African Journal of Economics)

Data-driven decomposition of seasonal time series - Heiler, Siegfried; Feng, Yuanhua (Journal of Statistical Planning and Inference)